Differential p38-dependent signalling in response to cellular stress and mitogenic stimulation in fibroblasts - Faust Dagmar (Cell Communication and Signaling, 2012)
Abstract p38 MAP kinase is known to be activated by cellular stress finally leading to cell cycle arrest or apoptosis. Furthermore, a tumour suppressor role of p38 MAPK has been proposed. In contrast, a requirement of p38 for proliferation has also been described. To clarify this paradox, we investigated stress- and mitogen-induced p38 signalling in the same cell type using fibroblasts. We demonstrate that - in the same cell line - p38 is activated by mitogens or cellular stress, but p38-dependent signalling is different. Exposure to cellular stress, such as anisomycin, leads to a strong and persistent p38 activation independent of GTPases. As a result, MK2 and downstream the transcription factor CREB are phosphorylated. In contrast, mitogenic stimulation results in a weaker and transient p38 activation, which upstream involves small GTPases and is required for cyclin D1 induction. Consequently, the retinoblastoma protein is phosphorylated and allows G1/S transition. Our data suggest a dual role of p38 and indicate that the level and/or duration of p38 activation determines the cellular response, i.e either proliferation or cell cycle arrest.